2021
DOI: 10.1186/s12967-021-02853-y
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus enhances cytotoxicity of natural killer cells against colorectal cancer via TLR3 pathway

Abstract: Background Cetuximab has been approved for use for first-line treatment of patients with wild-type KRAS metastatic colorectal cancer (CRC). However, treatment with cetuximab has shown limited efficacy as a CRC monotherapy. In addition, natural killer (NK) cell function is known to be severely attenuated in cancer patients. The goal of this study was to develop a new strategy to enhance antibody-dependent cell-mediated cytotoxicity (ADCC) mediated by NK cells, in combination with cetuximab again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…We previously established a method to obtain eNK cells from PBMC by co-culturing with K562-mBIL-21 feeder layer cells (Lifeark, China) for 2 weeks ( 23 ). Compared with other allogeneic cell sources, such as bone marrow and peripheral blood, cord blood (CB) is readily available as a frozen, “off the shelf” product, which provides more advantages as the starting material for cell therapies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established a method to obtain eNK cells from PBMC by co-culturing with K562-mBIL-21 feeder layer cells (Lifeark, China) for 2 weeks ( 23 ). Compared with other allogeneic cell sources, such as bone marrow and peripheral blood, cord blood (CB) is readily available as a frozen, “off the shelf” product, which provides more advantages as the starting material for cell therapies.…”
Section: Resultsmentioning
confidence: 99%
“…The cord blood mononuclear cells (CBMC) were isolated from the cord blood of 3 healthy donors by density gradient centrifugation. eNK were obtained by co-culturing CBMC with irradiation-inactivated K562 engineered cells for 14 days in the presence of IL-2 ( 23 ). The human ascites mononuclear cells were isolated from the ascites of 2 patients with malignant OC by Ficoll gradient density centrifugation, and the NK cells in ascites (AS_NK) were obtained using EasySep™ Human NK Cell Isolation Kit (Stemcell Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Another clinical trial of pancreatic cancer demonstrated that the combination of peptide pulsed DCs and poly-ICLC was safe and could induce a measurable tumor specific T cell population [ 150 ]. Additionally, reovirus-activated NK cells combined with cetuximab could synergistically enhance their antitumor cytotoxicity in colorectal cancer, which was dependent on TLR3 and its downstream signals [ 151 ].…”
Section: Rna Sensors In Cancer Immunotherapymentioning
confidence: 99%
“…Along this line, a recent study by Long and colleagues demonstrated that NK cells exposed to Cetuximab in combination with oncolytic reovirus were activated mainly by TLR-3 and showed increased ADCC against CRC lines in vitro independently to KRAS mutation status and EGFR expression level. Importantly, the combined exposure to reovirus and Cetuximab provided a greater NK-mediated anti-tumor effect than monotherapy with Cetuximab in vivo [ 182 ].…”
Section: Future Perspectivesmentioning
confidence: 99%